A novel once daily microparticulate dosage form comprising lansoprazole to prevent nocturnal acid breakthrough in the case of gastro-esophageal reflux disease: preparation, pharmacokinetic and pharmacodynamic evaluation. (8th January 2013) - Alai, Milind; Lin, Wen Jen
Abstract : The objective of this study was to formulate and evaluate the lansoprazole (LPZ)-loaded microparticles to prevent nocturnal acid breakthrough in the case of gastro-esophageal reflux disease (GERD). The microparticulate delivery system was prepared by solvent evaporation method using Eudragit RS100 as a matrix polymer followed by enteric coated with Eudragit S100 and hydroxypropyl methylcellulose phthalate HP55 using spray drying method. The enteric coated microparticles were stable in gastric pH condition. In vivo pharmacokinetic and pharmacodynamic studies in male Wistar rats demonstrated that enteric coated microparticles sustained release of LPZ and promoted ulcer healing activity. In other words, the microparticulate dosage form provided effective drug concentration for a longer period as compared to conventional extended release dosage form, and showed sufficient anti-acid secretion activity to treat acid related disorders including the enrichment of nocturnal acid breakthrough event based on a once daily administration.